Saat Artificial Intelligence (AI) Bertemu Akuntansi Syariah : Inovasi Cerdas atau Dilema Etis? - Arifa Kurniawan (Universitas Muhammadiyah Palembang, 2025)
This study aims to analyze the opportunities, challenges, and solutions of implementing artificial intelligence (AI) in Islamic accounting from an Islamic ethics perspective. The method applied is a literature review of academic sources related to AI, Islamic accounting, and Islamic ethics. The findings indicate that artificial intelligence (AI) can enhance efficiency, accuracy, and transparency in Islamic accounting practices, including transaction automation, compliance monitoring, and zakat management. However, challenges arise from algorithmic bias, lack of transparency, risks of Sharia non-compliance, and threats to maqashid al-shariah. The study concludes that artificial intelligence (AI) implementation should follow an Islamic ethical framework based on transparency, fairness, human accountability, and alignment with maqashid al-shariah. This approach ensures that artificial intelligence (AI) is not only technologically innovative but also consistent with Islamic values.